The Effect of Corporate Social Responsibility Disclosure and Intellectual Capital on Market Performance With Profitability as A Moderating Variable (An Empirical Study on Manufacturing Companies Listed on The Indonesia Stock Exchange In 2021–2023) - Komang Hellen Kirana Putri; I Ketut Jati (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Market performance reflects the firm's value from the perspective of investors, based on current performance and future projections, which influence stock prices and long-term investment returns. This study aims to examine the effect of Corporate Social Responsibility (CSR) disclosure and Intellectual Capital (IC) on market performance, with profitability as a moderating variable. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The sample consisted of 166 observations. The sampling method used in this study was non-probability sampling with a purposive sampling technique. Data were collected through documentation and analyzed using STATA software. The results show that CSR disclosure has no significant effect on market performance, while IC has a significant negative effect on market performance. However, profitability, measured by Return on Equity (ROE), significantly strengthens the relationship between CSR disclosure and market performance, as well as between IC and market performance."